Forecast heuristics, consumer expectations, and new-Keynesian macroeconomics: A horse race - Tae-Seok Jang; Stephen Sacht (Kiel University, Department of Economics, 2018)
This study extends the hybrid version of the baseline New-Keynesian model with heterogeneous agents who may adopt various forecast heuristics. With a focus on consumer expectations, we identify the most appropriate pairs of forecast heuristics that can lead to an equivalent fit to the data compared with the model specification under rational expectations. The competing specifications are estimated using the simulated method of moments. Our empirical results suggest that expectations under bounded rationality in the United States are grounded on consumers' emotional state, while for the Euro Area they are technical in nature. This observation questions the need for a hybrid model specification under rational expectations.
Keywords: C53; D83; E12; E21; E32; 330; Consumer Expectations; Forecast Heuristics; New-Keynesian Model; Simulated Method of Moments